2014
DOI: 10.1007/s00381-013-2351-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of pyramidal tract reorganization after pediatric stroke

Abstract: These results point to plastic reorganization of the pyramidal tract post-stroke and the utility of DTI in recognizing these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In the late stages of WD, cellular debris are removed, leading to increased water diffusion and subsequent slightly enhanced MD values (Maxwell et al, 2015). Our results were consistent with a previous study that revealed the FA value of the ipsilateral pyramidal tract in cerebral infarction patients on DTI was obviously decreased compared with the contralateral pyramidal tract on day 5 after onset, whereas there was no significant difference in MD between the two regions (George et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the late stages of WD, cellular debris are removed, leading to increased water diffusion and subsequent slightly enhanced MD values (Maxwell et al, 2015). Our results were consistent with a previous study that revealed the FA value of the ipsilateral pyramidal tract in cerebral infarction patients on DTI was obviously decreased compared with the contralateral pyramidal tract on day 5 after onset, whereas there was no significant difference in MD between the two regions (George et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The following parameters were set: diffusion-weighted images (DWI) with a maximum proliferationsensitive factor b value of 1000 s/mm 2 , field of view (FOV), 230 x 230 mm; matrix size, 256 x 256; slice thickness, 5 mm; number of layers, 23; and layer spacing, 1 mm. The DTI scan was performed using a single-shot Echo-Planar Imaging sequence with the following parameters: FOV, 230 x 230 mm; matrix size, 256 x 256; slice thickness, 3 mm; number of layers, 42; layer spacing, 1 mm; and TR/TE, 9825/131 ms. Diffusion was applied along at least six noncollinear directions with an axial DWI maximum proliferation-sensitive factor b value of 700 s/mm 2 (George et al, 2014).…”
Section: Examination Methodsmentioning
confidence: 99%
“…1), it indicated no motor function of the tracked aberrant fiber tracts. These aberrant fiber tracts could be technical artifacts of DTI tractography or the fiber tracts could exist but had no motor function [18,19]. Conversely, in patient 3motor activation area and CST fiber tract reorganized at SMA and anterior part of paracentral lobule, which is conserved the foot motor area, is consistent with ECS results.…”
Section: Discussionsupporting
confidence: 86%
“…1,34 In stroke studies, authors have proposed that preservation or recovery of the CST on DTI is mandatory for good recovery of impaired motor function. 15,20 However, the impact of LCD on surgical outcomes in patients with AVMs in eloquent areas has not been determined. 6 In recent years the feasibility of DTI in tracking fibers in AVM patients has been proven, although it has some methodological limitations.…”
Section: Discussionmentioning
confidence: 99%